Membangun Kepemimpinan dengan Hati untuk Meningkatkan Kinerja Manajerial Melalui Efikasi Diri dan Efektivitas Komunikasi di PT Perkebunan Nusantara III (Persero) - Siregar, Darmansyah; Lubis, Zulkarnain; Rahmadani, Vivi Gusrini; Sinulingga, Mehaga Bastanta; Aulia, Muhammad Reza (Universitas Teuku Umar, 2024)
Managerial performance varies greatly, as does leadership, with some having a significant influence and others having little to no impact. One way to improve managerial performance is by implementing heart-centered leadership. Therefore, it is necessary to study the influence of heart-centered leadership on managerial performance and related variables in palm oil companies. This research aims to analyze the influence of Heart-Centered Leadership on Self-Efficacy, Communication Effectiveness, and Managerial Performance at PT Perkebunan Nusantara III (Persero). The method used in this study is Partial Least Square (PLS) analysis, with steps including data preparation, building the model (path diagram, measurement model, and structural model), running the analysis using PLS algorithms and bootstrapping to test the significance of the paths, evaluating the measurement model by assessing reliability and validity, and evaluating the structural model to assess the strength of relationships between variables using R-square values and path coefficients, followed by result interpretation. The findings show that Heart-Centered Leadership influences Self-Efficacy and Communication Effectiveness but does not directly affect Managerial Performance. Self-Efficacy has an influence on Managerial Performance, but Communication Effectiveness does not. Heart-Centered Leadership has an indirect influence on Managerial Performance through Self-Efficacy.